Language and Brain: Maximizing Children’s Brain in Learning Foreign Language Through Storytelling, Songs, and Flashcards - Niswatin Nurul Hidayati (Ibriez: Jurnal Kependidikan Dasar Islam Berbasis Sains)
Early age is the age to play for children. In addition, early age is also a time when the child's brain is able to absorb many things. Therefore, using playing media to maximize the child's brain, especially in the field of language mastery is very important. Of course, there are many ways that can be used, but in this paper, the author focuses on the use of storytelling, songs, and flashcards as a medium to maximize foreign language learning in children. Language becomes one of the important things to be developed besides the cognitive domain. Learning foreign languages at an early age is considered good because it will stick in the brain of a child rather than learning it in adulthood. One part that is emphasized is related to the mastery of vocabulary that will become a provision for mastering other abilities, such as the ability to write, read, listen and speak.